STELLATE GANGLION BLOCK FOR THE IMMEDIATE TREATMENT OF FROSTBITE OF UPPER LIMB: Stellate Ganglion Block - Zaeem, Khalid; Janjua, Sarfaraz K; Arain, Inayatullah (Pakistan Armed Forces Medical Journal, 2008)
Objective: The purpose of performing early sympathectomy at high altitude was to get relief of vasoconstriction of frostbitten part so that the progression of the disease might be arrested immediately.Study Design: Descriptive Interventional Study.Place and Duration of Study: This study was done in Northern area from December 1997 to December 1998.Patients and Methods: In this interventional clinical trial, 23 young soldiers who were the victims of frostbite of upper extremity, were given stellate ganglion block with local anesthetic at army field hospital Goma, situated at altitude of 10,800 feet. All the patients were referred back from the posts at forward areas in high mountains, during one year (Dec 1997-Dec 1998).Results: The results of the study were very encouraging. Patients having mild to moderate form of disease recovered fully whereas disease progression was arrested in patients with severe form and later on they required less reconstructive surgery.Conclusion: The results noted in this study mandate the purpose of more research in this field so that the morbidity caused by the frostbite may be further decreased.